Pengaruh Penggunaan QRIS dan Gaya Hidup Konsumtif Terhadap Minat Menabung Gen Z di Kota Bandung - Azahra, Hanifa; Apriadi, Deri (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
The advancement of digital technology has transformed financial transaction patterns, particularly through the adoption of the Quick Response Code Indonesian Standard (QRIS). This study aims to examine the effect of QRIS usage and consumptive lifestyle on the saving interest of Generation Z in Bandung City. This research employed a quantitative approach with a survey method. Data were collected from 75 Generation Z respondents who use QRIS, obtained through online questionnaires. Multiple linear regression analysis was applied, preceded by classical assumption tests including validity, reliability, normality, as well as simultaneous (F) and partial (t) tests. The results reveal that QRIS usage has a positive and significant effect on saving interest, while consumptive lifestyle has no significant effect. Simultaneously, QRIS usage and consumptive lifestyle significantly influence saving interest among Generation Z. These findings highlight that QRIS, as a digital payment instrument, not only facilitates transactions but also holds potential to encourage healthier financial behavior among the younger generation.